Allometric relationship and development potential comparison of ports in a regional cluster: A case study of ports in the Pearl River Delta in China. (January 2020) - Chen, Jihong; Fei, Yijie; Wan, Zheng; Yang, Zaili; Li, Haobo; Choi, Kyoung-Suk; Xie, Xiaoke
Abstract: The development potential of a regional port cluster (RPC) is subject to the internal and external factors influencing port development. Port cargo throughput is an important internal factor, whereas import and export volume is a significant external factor. The growth rate of import and export volume is disproportionate to that of port cargo throughput. This study aims to measure the allometric relationship between the two abovementioned factors and establish a comprehensive development potential evaluation system on the basis of the RPC growth rate. This work uses a case study of the ports in China's Pearl River Delta, which is being greatly influenced by the framework agreement and outline of the development of the Greater Bay Area (GBA) in China. Findings reveal that import and export volume has a higher impact on port development potential than does port cargo throughput. In addition, Shenzhen has the highest development potential in terms of import and export volume, while Zhuhai Port has the highest potential in terms of port cargo throughput. Finally, an evaluation using the comprehensive development potential evaluation system shows that Shenzhen Port has the best comprehensive port development potential. Evaluating the development potential of ports in RPCs will offer useful insights that can be used by regional port company groups and relevant governmental authorities in making scientific decisions on port development and planning, especially in the crucial stage of the establishment of the GBA, and in rationally coordinating their development and minimizing unfair competition. Highlights: The development potential of a regional port cluster influences ports' development. An allometric growth model is proposed to evaluate the related factors. A case study of the ports in China's Pearl River Delta is developed. Historical data analysis provides decision-making basis for stakeholders.